INCREASING OEE THROUGH SIX BIG LOSSES ANALYSIS IN THE MACHINING PROCESS OF AUTOMOTIVE COMPANY - Kurbandi Satpatmantya BR; Syahrul Alim; RR. Wening Ken W (Jurnal Ilmiah Global Education, 2023)
This research was conducted at PT. Delta Bekasi. This study aims to improve Overall Equipment Effectiveness (OEE) in machining process in an automotive company by conducting Six Big Losses analysis. The method used is a case study with a qualitative and quantitative approach. Data was collected through direct observation, interviews and documentation. Data analysis carried out using the Overall Equipment Effectiveness (OEE) and Six Big Losses methods. The results of the study show that the OEE in the machining process at the automotive company is still low. After analyzing the Six Big Losses, factors causing production failures were found, such as downtime due to machine maintenance, long preparation times , and product defects. Based on the results of the analysis, several improvement steps are proposed, including: the use of preventive maintenance on machines, increasing the skills of machine operators, and improving the production process. By making improvements to the factors causing production failures, the OEE in the machining process at the automotive company increased from 82.24% to 85.39%. This shows that Six Big Losses analysis can help increase production efficiency and reduce downtime in automotive companies.